The sacred bridge - Hillerman, Anne, 1949- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2022)
Sergeant Jim Chee's vacation to beautiful Antelope Canyon and Lake Powell has a deeper purpose. He's on a quest to unravel a sacred mystery his mentor, the Legendary Lieutenant Joe Leaphorn, stumbled across decades earlier. Chee's journey takes a deadly turn when, after a prayerful visit to the sacred Rainbow Bridge, he spots a body floating in the lake. The dead man, a Navajo with a passion for the canyon's ancient rock art, lived a life filled with many secrets. Discovering why he died and who was responsible involves Chee in an investigation that puts his own life at risk.
Keywords: Manuelito, Bernie -- Fiction; Leaphorn, Joe, Lt. (Fictitious character) -- Fiction; Chee, Jim (Fictitious character) -- Fiction; Police -- New Mexico -- Fiction; Murder -- Investigation -- Fiction; Navajo Indians -- Fiction; Indian reservation police -- Fiction; Detective and mystery fiction; Thrillers (Fiction)